2014
DOI: 10.1002/humu.22545
|View full text |Cite
|
Sign up to set email alerts
|

A Frameshift Mutation inGRXCR2Causes Recessively Inherited Hearing Loss

Abstract: More than 360 million humans are affected with some degree of hearing loss, either early or later in life. A genetic cause for the disorder is present in a majority of the cases. We mapped a locus (DFNB101) for hearing loss in humans to chromosome 5q in a consanguineous Pakistani family. Exome sequencing revealed an insertion mutation in GRXCR2 as the cause of moderate to severe and likely progressive hearing loss in the affected individuals of the family. The frameshift mutation is predicted to affect a conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 21 publications
0
23
1
Order By: Relevance
“…It provides greater coverage and depth and is less expensive compared with WES. Over the past few years, mutations in several novel genes have been identified as causative factors for NSHL by WES15161819203233, which highlights the necessity for the updating and optimization of TES for inclusion of these new genes. Considering the over 70 known genes associated with NSHL and the genes that will be identified in the near future, TES might not actually be much cheaper than WES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides greater coverage and depth and is less expensive compared with WES. Over the past few years, mutations in several novel genes have been identified as causative factors for NSHL by WES15161819203233, which highlights the necessity for the updating and optimization of TES for inclusion of these new genes. Considering the over 70 known genes associated with NSHL and the genes that will be identified in the near future, TES might not actually be much cheaper than WES.…”
Section: Discussionmentioning
confidence: 99%
“…Whole exome sequencing (WES) has also been successfully used for analysis of genetic factors for hearing loss514, Additionally, WES has facilitated the identification of novel genes associated with Mendelian disorders including hearing loss151617. Recent studies have identified several causative genes for NSHL, including GPSM2, DNMT1, ELMOD3, GRXCR2 , and ADCY1 , by WES1516181920.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] It is estimated that more than 230 novel rare disease genes have been discovered to date using WES. 11 Several new NSHLcausative genes have also recently been revealed via WES, including GPSM2, DNMT1, BDP1, ELMOD3, TNC, GRXCR2, and ADCY1.…”
Section: Introductionmentioning
confidence: 99%
“…11 Several new NSHLcausative genes have also recently been revealed via WES, including GPSM2, DNMT1, BDP1, ELMOD3, TNC, GRXCR2, and ADCY1. [12][13][14][15][16][17][18] Thus, WES is a powerful approach for investigating the genetic basis of human disease.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its large capacity to survey the whole exome and genome in an unbiased manner, NGS is well suited to identifying the causative mutations of hereditary hearing loss. Novel genes and mutations for non-syndromic [Azaiez et al, 2014; Behlouli et al, 2014; Girotto et al, 2013; Imtiaz et al, 2014; Jaworek et al, 2013; Oh et al, 2014; Rehman et al, 2010; Santos-Cortez et al, 2013; Santos-Cortez et al, 2014; Schrauwen et al, 2012; Walsh et al, 2010; Xing et al, 2014; Zhao et al, 2013] and syndromic hearing loss [Pierce et al, 2010] have been identified using the NGS approach. Adding a targeted capture step prior to NGS enables the analysis of a focused subset of the whole genome, thereby reducing the required sequencing capacity and data management and analysis.…”
Section: Introductionmentioning
confidence: 99%